Low-FODMAP diet on postprandial distress syndrome type of functional dyspepsia with mixed type of irritable bowel syndrome patient: A case report - Djatioetomo, Anastasia K.; Maharani, Andi RK.; Djatioetomo, Yovita CED.; Nurrochmawati, Zidny; Anandita, Faizal A. (Narra Sains Indonesia, 2024)
Functional dyspepsia is a complex collection of symptoms from the gastroduodenal, while irritable bowel syndrome (IBS) is a disease that chronically weakens gastrointestinal. The occurrences of both of these diseases are common; however, the new approach therapy introducing the low-FODMAP diet (low fructose, oligosaccharides, disaccharides, monosaccharides, and polyols) is rarely discussed. The aim of this case report was to present a case of functional dyspepsia with IBS mixed type treated with a low-FODMAP diet. A female 37 years old reported complaints of heartburn worsening over the last seven months. Based on IBS-symptom severity scale (IBS-SSS) assessment, the patient had 75% scale on belly pain and 50% abdominal distention, which interfered the daily activity significantly. The patient was diagnosed with functional dyspepsia subtype postprandial distress syndrome with IBS mixed type. In addition, the low-FODMAP diet was started immediately, together with pharmacological therapy (oral omeprazole and domperidone), and followed up each week. On the first week of evaluation, the patient was feeling much better as IBS-SSS assessment scores decreased, and the pharmacological therapy was stopped. On the second week of evaluation, the patient had no more complaints with IB-SSS assessment markedly decreased. This case highlights that low-FODMAP diet could be a new approach therapy for IBS that could improve the IBS symptoms.